2014
DOI: 10.1016/j.fbp.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of phycocyanin microcapsules and its properties

Abstract: a b s t r a c tPhycocyanin was microencapsulated by an extrusion method using alginate and chitosan as coating materials. This work was aimed to optimize the encapsulation process, characterize the physicochemical properties of microcapsules, and evaluate the storage stability and in vitro release performance. The optimum process conditions for preparing microcapsule gained from the single factor experiments were as follows: alginate content 2.5%, ratio of phycocyanin to alginate 1.5:1, content of calcium chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 26 publications
1
36
0
9
Order By: Relevance
“…The encapsulation efficiency of microencapsulated TP was calculated following the method of Yan et al (2014). The TP content on the surface of the microcapsules and the total TP of microcapsules were determined by the Folin-Ciocalteu method described by Zheng et al (2011).…”
Section: Determination Of Encapsulation Efficiency Of Microencapsulatmentioning
confidence: 99%
“…The encapsulation efficiency of microencapsulated TP was calculated following the method of Yan et al (2014). The TP content on the surface of the microcapsules and the total TP of microcapsules were determined by the Folin-Ciocalteu method described by Zheng et al (2011).…”
Section: Determination Of Encapsulation Efficiency Of Microencapsulatmentioning
confidence: 99%
“…[23,25] Besides optimizing the physical and chemical parameters mentioned above, phycocyanin microencapsulation has been developed to improve the storage stability of phycocyanin. [28] The phycocyanin used in bioactivity studies usually of the high purity, and few reports have investigated food-grade phycocyanin. To enhance the storage stability and maintain the quality of phycocyanin, the anti-microbial agent sodium azide (NaN 3 ) and the protein reducing agent dithiothreitol (DTT) are commonly used as preservatives in C-phycocyanin (CPC) for analytical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The microspheres were elaborated based on the study reported by Yan et al 10 with some adaptations. A sodium alginate solution (15 g.L −1 ) was prepared by dissolving it in distilled water at 24°C, and dilution was performed at 1,890 g on a magnetic stirrer for 12 h. After obtaining a homogeneous solution of the sodium alginate, the Spirulina biomass (37 g. L −1 of alginate solution) was added and homogenized for 30 min.…”
Section: Methodsmentioning
confidence: 99%